Mechanics of the Kalabagh Fault, northwest Himalayan fold and thrust belt (convergence zone of India and Eurasia), using SAR interferometry and CFS - Zafar, Waqar Ali; Javed, Farhan; Ahmed, Rizwan; Ehsan, Muhsan; Abdelrahman, Kamal; Fnais, Mohammed S.; Qureshi, Mansoor Aziz (Frontiers in Earth Science, 2023)
The Kalabagh strike-slip fault, which is characterized by right-lateral movement, is part of the North Western Himalayan Foreland Fold and Thrust Belt in Pakistan. This structure marks the western and eastern terminations of the Salt Range and Surghur Ranges, respectively. No significant (>M6) earthquakes have been reported along the Kalabagh fault in recent decades. Here, we take advantage of space-borne Sentinel-1A SAR interferometry to gain insight into the mechanics of faulting, aseismic creeping and stress loading of the seismic cycle on the Kalabagh fault spanning over approximately 7 years. In this study, we also removed the tropospheric effects using the GACOS(i.e.,Generic Atmospheric Correction Online Service ) data from the rate-map. We further resolved the LOS deformation in to both horizontal and vertical deformation. Our beyesian inversion indicates that the fault experiences significant horizontal and vertical displacements. The fault's southern and northern segments exhibit a creeping rate of approximately ~4.2±1.3 to 4.8±1.6 mm/year, while the central section does not display any horizontal creeping. We found the creeping is confined between 0 and ~2.7±1.1 km depth at northern section and 0 and ~3.9±1.1 km on the southern section of the faults. Nevertheless, we find the vertical creeping of ~10 mm/year confined between 0.5 to 6 km depth in the central segment of the fault. Moreover, our model does not resolve the interseismic slip at depth on the Kalabagh fault. our results affirm that Kalabagh fault is creeping and the internal deformation due to presence of thick salt layer over the decollement facilitate the creeping on this fault. In addition, coulomb stress modelling depicts that the creeping on the Kalabagh fault increase the coulomb stress changes in the northern section of the KBF.